(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Chronic Idiopathic Urticaria (CIU) has an estimated prevalence of 35-65% and impacts 15 to 25% of the population at some point in their lives. Studies have shown the possible involvement of Helicobacter pylori (H. pylori) infection in chronic idiopathic urticaria (CIU), but the relationship remains controversial. Objective: To quantitatively assess the association between H. pylori infection and chronic idiopathic urticaria. Materials and Methods: This was a case-control type of analytical study and 100 patients were enrolled fifty patients of CIU fulfilling inclusion criteria with no identifiable cause were taken as case and patients without urticaria were taken as control, attending in the department of Dermatology & Venereology, CMH Dhaka for treatment from May 2015 to Aug 2016. Helicobacter pylori infection was confirmed by serum IgG for H. pylori test. Results: The result showed that H. pylori infection significantly affected a high percentage of patients 30 (60%) with chronic idiopathic urticaria. Male respondents were more positive 16(53.3%) than female 14(46.7%), in the middle aged 31-50 year about 18(60%) and triple drug therapy was successful in 16(53.33%) patients in whom H. pylori was detected. Conclusion: Urticaria is a common clinical disorder with complex triggering factors. Chronic urticaria has provided evidence that enteric infection with H. pylori may induce the disease. In this case control study, it was evident that chronic idiopathic urticaria was associated with positive serum IgG for H. Pylori. A trial of H. pylori eradication therapy may be offered to patients with CIU and evidence of H. pylori infection. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 122-126